Analisis Rasio Keuangan Pemerintah Daerah Provinsi Lampung pada Kinerja Keuangan Daerah - Arini, Arini; Erliana, Ria (Jurnal IAKP: Jurnal Inovasi Akuntansi Keuangan & Perpajakan, 2023)
The analysis of the financial ratios of local governments serves as a foundation for evaluating the financial performance of the respective regions, providing a basis for decision-making by local authorities. The aim of this research is to assess the financial performance of the Provincial Government of Lampung based on five financial ratios. The analytical technique employed is quantitative descriptive analysis, guided by secondary data derived from the realization reports of the Lampung Provincial Government's Regional Budget (APBD) for the fiscal years 2016–2022. The analysis results reveal fluctuations in various financial indicators during the period from 2016 to 2022. The degree of fiscal autonomy (DOF) experienced a significant increase in 2022, reaching an excellent level. The overall financial capacity is generally good to very good, indicating a solid ability to manage regional finances. The effectiveness of regional original income (PAD) exhibits fluctuations, requiring further evaluation to identify the factors influencing these fluctuations. The efficiency of regional financial management is also variable, with an overall average level of efficiency. The ratio of the harmony between regional expenditure and capital expenditure tends to be low, indicating a budget allocation that is more focused on operational expenses. Proposed recommendations include improving the effectiveness of PAD, monitoring efficiency, enhancing the budget allocation for capital expenditure, and maintaining transparency and accountability in budget allocation. Through these measures, the Provincial Government of Lampung can enhance its regional financial management, support sustainable growth and development in the area, and provide better services to the community.Keywords: APBD, financial performance, Lampung, financial ratios